Stages of Financial Literacy among Women Entrepreneurs in Batang and Pekalongan - Ningtyas, Jilma Dewi Ayu; Olivya, Anggiya Misti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This research aims to examine the financial literacy and financial management of women entrepreneurs who are members of the Indonesian Women Entrepreneurs Association (IWAPI) in Batang and Pekalongan Regencies. Using a qualitative approach, this research analyzes aspects of financial knowledge, behaviour and skills, as well as motivation and self-confidence in running a business. The research results show that financial literacy has a vital role in supporting the sustainability of women entrepreneurs' businesses. Financial literacy and good financial management are very necessary for business continuity. Even though their level of financial literacy is considered adequate, there are areas that still require improvement, especially in the use of digital technology for financial management. More structured financial management will help women entrepreneurs optimize income and maintain the sustainability of their businesses. Further research is recommended to expand the subject of study not only to IWAPI members but also to women entrepreneurs in other organizations to gain broader insight into the challenges and needs in managing women's business finances in Indonesia.